Students’ Communicative Competence: A Descriptive Study In English Education Program At STKIP Taman Siswa Bima - Suratman; Dewi Ernawati; Ratnah (STKIP Taman Siswa Bima, 2017)
Students’ Communicative Competence: A Descriptive Study in English Education Program at STKIP Taman Siswa Bima. The Objective of Study IS To describe the students communicative competence. AND To describethe factors that affect their communicative competence. In this research, the writer used qualitative descriptive method. According to Ary (1997: 219) about qualitative descriptive is design to obtain information concern the current status of phenomena and he also states that the qualitative data is described by sentences Based on the data findings above, the writer found 13 tottaly data which devided into 7 the students weakness in communicative competence especially about sociolinguistic competence and 6 factors that influences the students weakness in communicative competence especially about sociolinguistic competence. The students’ weakness in communicative competence especially about sociolinguistic competence.